Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio (CAR), dan Non Performing Financing (NPF) Terhadap Likuiditas Perbankan Syariah Di Indonesia Tahun 2015-2019 - Kurniawan Yogi Saputro; Arini Wildaniyati (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
Abstract— This study aims to determine the effect of Third Party Funds on Liquidity, the effect of Capital Adequacy Ratio (CAR) on Liquidity, the effect of Non Performing Financing (NPF) on Liquidity, and the influence of Third Party Funds, Capital Adequacy Ratio (CAR), and Non Performing Financing ( NPF) against Liquidity. The sampling technique used was purposive sampling technique. The data obtained comes from secondary data in the form of banking annual financial reports for 2015-2019 which are downloaded from the official website of the bank concerned. Data analysis was performed using descriptive statistics, classical assumption test, multiple linear regression analysis, determinant coefficient test, t test and F test. The results of the hypothesis research indicate that the Third Party Funds variable is 0,000, the Capital Adequacy ratio (CAR) variable is 0.013, the variable NonPerforming Financing is 0.196, and simultaneously is 0.000. With these results it can be stated that only Third Party Funds, Capital Adequacy Ratio (CAR) have a positive and significant effect on Liquidity, while Non Performing Financing (NPF)  has no positive and significant effect on liquidity. Simultaneously, Third Party Funds, Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), have a positive and significant effect on liquidity. Keywords—: Third Party Funds; Capital Adequacy Ratio, Non Performing Financing, and Liquidity.